PENGARUH KEPERCAYAAN DAN KEAMANAN TERHADAP NIAT UNTUK BERTRANSAKSI MENGGUNAKAN SISTEM E-COMMERCE (STUDI KASUS PADA MAHASISWA PROGRAM STUDI S1 AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TADULAKO) - Shabrina, Nur Rahma; Indriasari, Rahayu; Mapparessa, Nurlaela (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2020)
This study aimed to determine and analyze the influence of trust and security over the intention to transact using e-commerce This research is a quantitative research using primary data. The sample of this study were students of accounting study program that amounted to 71 respondents. The results showed that simultaneously, trust and security significantly influenced the intention to transact using e-commerce system. Trust partially had significant influence the intention to transact using e-commerce system. Security partially had significant influence the intention to transact using e-commerce system.